“Eu sei o que sou e o que não sou”: Música pop, cultura e identidade a partir de Madame X de Madonna - Monteiro, Gabriel Holanda (2023)
The following research proposes to think, problematize and materialize the representations that pop music constructs about cultures (involving their asymmetrical power relations) and the legitimizing and resistance identity groups, based on gender, race, sexuality and (de)coloniality markers. Three Madonna music videos (God Control, Dark Ballet and Batuka), works that belong to Madame X, album released by the artist in 2019, are adopted as objects. In order to observe the cultural dynamics expressed in the relations between the images, the chosen methodological proposal consists of the articulation of the theoretical-methodological foundation of the Tartu-Moscow Semiotic School (TMSS) with imagery experimentations inspired by the plates of the Atlas Mnemosyne, Aby Warburg’s unfinished project. The analysis starts from the music videos in question to observe them as cultural texts that gain new meanings when juxtaposed to images from distinct cultural, mediatic, local and temporal contexts. The theoretical framework is mainly composed of works that discuss massive popular music, pop music, culture, semiosphere, nucleus, periphery, border, identity, gender, race, sexuality and post-colonialism. The investigation gave rise to four main results: 1) the identification of three different modes of representation adopted by music’s cultural industry in music videos: the protagonism of the representing artist, the mediated protagonism of the represented subject/group and the mediated sharing of protagonism between the representing artist and the represented subject/group; 2) the finding that the TMSS and the Atlas Mnemosyne proved to be a powerful combination for a methodological proposal in line with the research’s problem and goals; 3) the observation that appropriation (as the act of picking up signs of a given culture or identity group and articulating them in one's own production) is the cultures’ main mechanism of representation and construction of meaning, which gives rise to cultural conflicts, clashes, suffering, encounters, dialogues, silencing, violence, colonizations, oppressions, counter-attacks, resistance, legitimations and estrangement; 4) the mounting of nine thematic image plates that allowed the examination of such dynamics within the scope of culture from the three analyzed video clips. Special thanks to CAPES for the funding that facilitated access to readings, materials and other essential activities for carrying out the research.Keywords: Massive popular music. Culture. Identity. Image. Madonna.